Difficulties of wooden housing production sector in Brazil - De Araujo, Victor A.; Vasconcelos, Juliano S.; Morales, Elen A. M. [UNESP]; Savi, Antonio F. [UNESP]; Hindman, Daniel P.; O'Brien, Michael J.; Negrao, Joao H. J.; Christoforo, Andre L.; Lahr, Francisco A. R.; Cortez-Barbosa, Juliana [UNESP]; Gava, Maristela [UNESP]; Garcia, Jose N. (Taylor & Francis Ltd, 2020)
This research identified the central hindrances found in Brazilian wooden housing scenario in the fields of finished product, producer, and sector. Thus, a questionnaire with three qualitative questions based on multiple-choice answers allowed investigating the difficulties faced by these producers in Brazil. This sector still faces obstacles in the three observed fields, especially for the negative aspects of house financing, housing technique certification, skilled hand labour, general costs incurred in local production, tax exemptions, public policies, utilization of wooden houses in public works, and other factors. These obstacles in wooden housing sector have created limitations of production potential and restrictions of its market. A current panorama from these obstacles was formed, which could contribute with sectoral development. Actions such as creation and institution of incentives and specific policies should consolidate as the main direction to reduce these difficulties faced by the wooden housing producers.
Keywords: Hindrances; timber industry; wooden construction; sectorial research; personal interview; sustainable utilization of forest products